ANALISIS ANGGARAN BIAYA OPERASIONAL DAN ANGGARAN PENDAPATAN TERHADAP KINERJA KEUANGAN BERDASARKAN RETURN ON ASSET (ROA) PADA PT MADUBARU YOGYAKARTA TAHUN 2012-2016 - Aryatama, Sigit; Ismanto, Deny (Jurnal Fokus Manajemen Bisnis, 2017)
This study aims to determine the presence or absence of influence operational cost budget and revenue budget to financial performance based on return on assets (ROA) at PT Madubaru Yogyakarta in the year 2012-2016. In this study there are three variables, namely budget operational (X1), revenue budget (X2), and ROA (Y). Research methods what I use is the quantitative analysis method, the type of data it uses secondary data, data collection techniques used are documentation and Interview. Data analysis techniques using multiple linear regression with SPSS program version 20. The results showed that the budget Operational and income budgets affect return on assets (ROA) seen with an R value of 0.962. Partially operational budget has no effect on ROA and income budget has an effect on ROA.